Could MicroRNAs be Regulators of Gout Pathogenesis? - Yangang Wang (Cellular Physiology and Biochemistry, 2015)
MicroRNAs (miRNAs) are a class of noncoding RNAs that mainly negatively regulate gene expression. miRNAs have important roles in many diseases, including inflammatory diseases. Gout is a common arthritis caused by deposition of monosodium urate crystals within joints. Recent studies suggested that miRNAs may be involved in the development of inflammatory arthritis, including acute gouty arthritis. In the present review, we systemically discuss relevant publications in order to provide a better understanding on the possible role of miRNAs in gout. miRNAs may act as regulators of gout pathogenesis via several pathways. Targeting miRNAs may be a promisingstrategy in the treatment of gout.